Targeted Next-Generation Sequencing Identifies Separate Causes of Hearing Loss in One Deaf Family and Variable Clinical Manifestations for the p.R161C Mutation in SOX10 - Xiaoyu Yu; Yun Lin; Hao Wu (Neural Plasticity)
Hearing loss is the most common sensory deficit in humans. Identifying the genetic cause and genotype-phenotype correlation of hearing loss is sometimes challenging due to extensive clinical and genetic heterogeneity. In this study, we applied targeted next-generation sequencing (NGS) to resolve the genetic etiology of hearing loss in a Chinese Han family with multiple affected family members. Targeted sequencing of 415 deafness-related genes identified the heterozygous c.481C>T (p.R161C) mutation in SOX10 and the homozygous c.235delC (p.L79Cfs∗3) mutation in GJB2 as separate pathogenic mutations in distinct affected family members. The SOX10 c.481C>T (p.R161C) mutation has been previously reported in a Caucasian patient with Kallmann syndrome that features congenital hypogonadotropic hypogonadism with anosmia. In contrast, family members carrying the same p.R161C mutation in this study had variable Waardenburg syndrome-associated phenotypes (hearing loss and/or hair hypopigmentation) without olfactory or reproductive anomalies. Our results highlight the importance of applying comprehensive diagnostic approaches such as NGS in molecular diagnosis of hearing loss and show that the p.R161C mutation in SOX10 may be associated with a wide range of variable clinical manifestations.